Land-Use and Land-Cover Changes and Urban Expansion in Central Vietnam: A Case Study in Hue City - Nguyen Hoang Khanh Linh; Tung Gia Pham; Ty Huu Pham; Chau Thi Minh Tran; Tan Quang Nguyen; Nam Thang Ha; Nguyen Bich Ngoc (Urban Science)
During the past two decades, Hue city has undergone significant changes in its economic development, leading to a rapid transformation of its land-use and land-cover (LULC) patterns. This study used remote sensing data and Geographic Information Systems (GIS) to analyze changes in the land-use and land-cover in Hue city, providing essential insights for the city’s future development. This research examines indicators such as area and land-cover changes, urban development trends, and the morphology of urban areas during the period from 2000 to 2020, with assessments conducted at ten-year intervals. The results showed that built-up and forest land have increased, while agricultural and unused land have decreased over time. By 2020, the urban area had expanded by more than 60% in the north and northeast directions. Hue city developed through infilling and edge expansion of existing urban areas, while some regions primarily expanded into outlying sections in the east and south by constructing high-end residential areas on former paddy rice fields. These findings yield valuable policy implications that extend beyond the case study of Hue city, offering insights for other cities to pursue inclusive and prosperous futures.